Three-Dimensional Heterogeneity of Cerebellar Interposed Nucleus-Recipient Zones in the Thalamic Nuclei - Ma, Kuang-Yi; Cai, Xin-Yu; Wang, Xin-Tai; Wang, Zhao-Xiang; Huang, Wan-Meng; Wu, Zhi-Ying; Feng, Zhou-Yan; Shen, Ying (Neuroscience bulletin, 2021)
The cerebellum is conceptualized as a processor of complex movements and is also endowed with roles in cognitive and emotional behaviors. Although the axons of deep cerebellar nuclei are known to project to primary thalamic nuclei, macroscopic investigation of the characteristics of these projections, such as the spatial distribution of recipient zones, is lacking. Here, we studied the output of the cerebellar interposed nucleus (IpN) to the ventrolateral (VL) and centrolateral (CL) thalamic nuclei using electrophysiological recording in vivo and trans-synaptic viral tracing. We found that IpN stimulation induced mono-synaptic evoked potentials (EPs) in the VL but not the CL region. Furthermore, both the EPs induced by the IpN and the innervation of IpN projections displayed substantial heterogeneity across the VL region in three-dimensional space. These findings indicate that the recipient zones of IpN inputs vary between and within thalamic nuclei and may differentially control thalamo-cortical networks.